2011
DOI: 10.1111/j.1365-2850.2011.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent client views towards the treatment of anorexia nervosa: a review of the literature

Abstract: This paper reviews current literature in which adolescents with anorexia nervosa (AN) were consulted about their views of their treatment. Published research was systematically retrieved and interrogated during 2009-2010 and analysed using a four-stage model. Eleven studies met the inclusion criteria. Three core themes were identified. AN was perceived as a means of taking control and also something that controlled the individual. Tensions were recognized between client preferences for psychological interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 44 publications
(89 reference statements)
4
49
0
Order By: Relevance
“…Smith et al, 2014). For example in their review of qualitative studies examining the views of adolescent clients towards AN treatment, Westwood and Kendal (2012) found a clear preference for treatment:…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al, 2014). For example in their review of qualitative studies examining the views of adolescent clients towards AN treatment, Westwood and Kendal (2012) found a clear preference for treatment:…”
Section: Discussionmentioning
confidence: 99%
“…We then searched each database for studies that were tagged with both alliance and EDs controlled-vocabulary terms. Lastly, we mined the reference section of eight review articles relevant to alliance in EDs which we identified via the initial electronic database search (Fassino & Abbate-Daga, 2013;Manlick, Cochran, & Koon, 2013;Martin et al, 2011;Shirk et al, 2011;Vitousek & Watson, 1998;Vocks et al, 2010;Westwood & Kendal, 2012;Wilson, 2011) for any additional relevant studies that may have been missed.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The PsychINFO terms for EDs were eating disorders, anorexia, bulimia, binge eating disorder, EDNOS, and eating disorder not otherwise specified. We then searched each database for studies that were tagged with both alliance and EDs Manlick, Cochran, & Koon, 2013;Martin et al, 2011;Shirk et al, 2011;Vitousek & Watson, 1998;Vocks et al, 2010;Westwood & Kendal, 2012;Wilson, 2011) for any additional relevant studies that may have been missed.The electronic database search combined with the hand search of the review articles resulted in an initial candidate study pool of 787 studies. These studies were then reduced in a stepwise fashion by two independent coders (the first and second authors), as described in the PRISMA diagram (Figure 1).…”
mentioning
confidence: 99%
“…Education, training and support assists nurses to overcome these challenges, enhancing capac-ity for therapeutic interaction (Koekkoek et al, 2012;Surtees, 2007;Thurston, 2003;van Meijel et al, 2009). Education and training enhances nursing skills, knowledge, awareness, insight and attitudes, leading to an improved ability to establish and maintain a therapeutic alliance (Brown & Wissow, 2012;Byrne & Deane, 2011;Dickinson & Hurley, 2011;Hewitt & Coffey, 2005;O'Baugh et al, 2009;Ramjan, 2004;Simpson, 1999;van Meijel et al, 2009;Westwood & Kendal, 2012). Nursing education also enhances the capacity for evidence-based practice (Anderson & Funnell, 2008;Cameron et al, 2005;Surtees, 2007).…”
Section: Nursing Support and Educationmentioning
confidence: 91%